INTEGRATING DIGITAL READABLE APPLICATIONS TO FOSTER STUDENTS' MOTIVATION IN ENGLISH READING - Andi Muhammad Yauri; Kasmiati Kasmiati; Hasriati Nur; Andi Adisaturrahimi; Muhammad Zuhri Dj (Linguists : Journal of Linguistics and Language Teaching, 2025)
As a successful strategy for raising students' interest and engagement, the use of digital resources in language learning has grown in significance. The purpose of this study is to look into how incorporating Readable applications affects students' motivation to read in English. Thirty eleventh graders from Bone, Indonesia, public senior high school participated. Using a pre-experimental design and a quantitative methodology, the data was gathered via a motivation survey and statistically examined. A higher mean score and a statistically significant difference (p < 0.05) between pre- and post-test results demonstrated that students' enthusiasm to read English texts was greatly enhanced by using Readable applications. These results imply that digital reading platforms might provide a more engaging and dynamic learning environment that encourages students' independence and curiosity. The study advises teachers to include similar digital tools into their teaching practices and emphasizes the pedagogical implications of technology-enhanced learning in tackling motivating issues in EFL reading classrooms.